63. Frequency and Outcomes of Patients Prescribed Antibiotics for Extended Durations on Discharge from the Hospital to Nursing Homes. (31st December 2020) - Molina, Kaitlyn E; Noble, Brie N; Crnich, Christopher J; McGregor, Jessina C; Bearden, David T; Chan, Dominic; Furuno, Jon P; Furuno, Jon P
Abstract: Background: Nursing home (NH) residents are at increased risk of being prescribed antibiotic for extended durations and experiencing antibiotic-associated adverse events. However, many of these antibiotics are prescribed in the hospital prior to NH admission. We quantified the frequency, characteristics and outcomes of patients receiving antibiotic treatment in the hospital and discharged to NHs with an antibiotic prescription for greater than 7 days. Methods: This was a retrospective cohort study of adult (age > 18 years) patients with a prescription for an antibiotic on discharge from Oregon Health & Science University Hospital (OHSU) to a NH between January 1, 2016 and December 31, 2018. Study data were collected from an electronic repository of patients' electronic health record data. Outcomes of interest included having an emergency department (ED) visit, inpatient hospital admission, or inpatient admission for Clostridioides difficile infection (CDI) at the index facility within 30 days of discharge. Results: Among 2969 antibiotic prescriptions on discharge, 1267 (42.7%) were prescribed for greater than 7 days to a total of 1059 patients. A diagnosis of a bacterial infection was present for 902 (85.2%) patients. The most frequent diagnoses were bloodstream/endocarditis (21.8%), osteomyelitis (11.6%), and skin and soft tissue infections (10.6%). The most frequently prescribed antibiotics were cephalosporins (24.2%), penicillins (14.1%), glycopeptides (12.9%), and fluoroquinolones (12.6%). Of the 1059 identified patients, 126 (11.9%) had an ED visit, 216 (20.4%) inpatient admission, and 16 (1.5%) had an admission for CDI within 30 days of discharge. Conclusion: More than 40% of antibiotic prescriptions on discharge to a NH were for greater than 7 days. This frequency and associated poor outcomes suggest extended antibiotic duration are a high-value target to improve antibiotic prescribing on discharge to NHs. Disclosures: All Authors : No reported disclosures